Fine Grained Access Control Policy with Advanced Encryption Standard in the Cloud Computing - Keerthi Chennam, Krishna; Mudda, Lakshmi (International Journal of Engineering and Technology, 2018)
The Data Base as a Service is a great example where the database engine and storage devices are in cloud data. This scheme allows customers to outsource data and store in cloud database on pay per user, scalable and flexible. But data confidentiality is in high risk when data is outsourced and stored in third party database. A trusted third party server must be maintaining the third party data base. There is a possibility of malicious administrator who can leaks the data which is stored in third party database. The best method is to encrypt the data and store in third party database but alone encryption is not sufficient. Even authorization is another problem that who can access the data. For data security and authorized of users, the fine grained access control policy Cipher text policy Attribute Based encryption (CP-ABE) is used to give access to authorized users only and the best symmetric encryption Advanced Encryption Standard(AES) is applied on data before outsourcing the data in cloud.Â
Keywords: CP-ABE; AES; Cloud Data Base; Data Security; Access Control Policy.